Pengaruh Pertumbuhan Penjualan, Likuiditas, Risiko Bisnis, Profitabilitas & Struktur Aset Terhadap Struktur Modal Pada Perusahaan Sektor Properti yang terdaftar di Bursa Efek Indonesia - Arie Pratania Putri; Jovian Cheserio; Katherine Katherine; Celine Celine; Jeslin Jeslin (Owner : Riset dan Jurnal Akuntansi, 2021)
This research was conducted in order, so we can find out how much influence the variable x on variable y. The independent variable (x) on this research are Sales Growth, Liquidity, Business Risk, Profitability, Asset Structure and the variable (y) is Capital Structure. The population in this research was taken from the property sector companies. This research used purposive sampling technique in order to find out the total sample, and the total is 132 samples. This research also used the Z-Score method, which used to remove the extreme data (abnormal data), which is equals to 15 samples, that means the final number in this research is 117 samples, and the data analysis used multiple linear regression, namely the coefficient of determination (R2), simultaneous (F test), partial (t test). And the result of the t test (partial) are Sales Growth, Liquidity doesn’t have a significant effect on Capital Structure, then Business Risk, Asset Structure has a significant effect on Capital Structure, and Profitability has no effect, but the significant on the Capital Structure of Property Sector Companies that listed on the Indonesia Stock Exchange between 2014 until 2017, the result of F test (simultaneous) is, all of the X variable are taking effect with variabel Y.